2020
DOI: 10.1177/0300060520963993
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol ameliorates radiation-induced brain injury via the activation of SIRT3

Abstract: Objective Sirtuin 3 (SIRT3) plays a vital role in regulating oxidative stress in tissue injury. The aim of this study was to evaluate the radioprotective effects of honokiol (HKL) in a zebrafish model of radiation-induced brain injury and in HT22 cells. Methods The levels of reactive oxygen species (ROS), tumor necrosis factor-alpha (TNF-α), and interleukin-1 beta (IL-1β) were evaluated in the zebrafish brain and HT22 cells. The expression levels of SIRT3 and cyclooxygenase-2 (COX-2) were measured using wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…The protective effects of each pharmacologic agent in diminishing oxidant-induced AEC mtDNA damage parallel our findings using a genetic approach to augment AEC SIRT3 expression [32]. Our observation that honokiol protection against oxidant-induced AEC mtDNA damage occurs in a SIRT3-dependent manner concurs with prior studies showing that honokiol's protective effects are dependent upon SIRT3 in ameliorating murine bleomycin-induced pulmonary fibrosis [37], doxorubicin-induced cardiomyopathy [49], diabetes-induced myocardial dysfunction [51], and radiation-induced brain injury [52]. Although the mechanism by which SIRT3 reduces mtDNA damage was not explored in this study, prior studies have established that SIRT3 can reduce mtROS levels and enhance mtDNA repair in a variety of cell types [24][25][26][27][28][29]32,33,53,54].…”
Section: Discussionsupporting
confidence: 88%
“…The protective effects of each pharmacologic agent in diminishing oxidant-induced AEC mtDNA damage parallel our findings using a genetic approach to augment AEC SIRT3 expression [32]. Our observation that honokiol protection against oxidant-induced AEC mtDNA damage occurs in a SIRT3-dependent manner concurs with prior studies showing that honokiol's protective effects are dependent upon SIRT3 in ameliorating murine bleomycin-induced pulmonary fibrosis [37], doxorubicin-induced cardiomyopathy [49], diabetes-induced myocardial dysfunction [51], and radiation-induced brain injury [52]. Although the mechanism by which SIRT3 reduces mtDNA damage was not explored in this study, prior studies have established that SIRT3 can reduce mtROS levels and enhance mtDNA repair in a variety of cell types [24][25][26][27][28][29]32,33,53,54].…”
Section: Discussionsupporting
confidence: 88%
“…SIRT3 resides in the mitochondria and represents a multifunctional deacetylase regulating the acetylation state of the mitochondrial protein involved in MQC [56]. Liao et al [57] found that honokiol treatment increased the ability of SIRT3 to repress the expression of COX-2 and pro-inflammatory cytokines, thus mitigating radiation-induced brain injury in a zebrafish model. SIRT3 deficiency elevated the expression of IL-1β, TNF-α, and COX-2, and increased microglial proliferation and activation [58].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated honokiol-mediated SIRT3 activation in vivo in choline-deficient HFD-fed mice [ 168 ] and carbon tetrachloride (CCl4)-stimulated liver-damaged mice [ 169 ] and in cultured primary mouse cardiomyocytes [ 170 ] and AML12 hepatocytes [ 168 ]. Using a zebrafish model of radiation-induced brain injury and HT22 cells, Liao et al observed the neuroprotective effects following honokiol treatment via suppression of ROS, TNF-α, IL-1β, and Cox2, and elevated Sirt3 expression [ 171 ].…”
Section: Translational Significance Of Sirt3 Activationmentioning
confidence: 99%